Burden and distribution of venous thromboembolism across cancer types and stages: a meta-analysis of observational studies - Singh, Vikram; Tabassum, Heena; Kohli, Simran; Rulu, Peteneinuo; Aggarwal, Sumit (Frontiers in Oncology, 2025)
IntroductionVenous thromboembolism (VTE) is a serious life-threatening complication among patients with cancer. This systematic review and meta-analysis aimed to quantify the proportion of VTE across different cancer types, stages, and study settings.MethodsA comprehensive literature review was conducted to identify observational studies reporting VTE events in cancer patients. Studies were categorized into population-based and hospital-based settings to compare VTE prevalence. Cancer types were classified by anatomical origin, and cancer stages (Stage I–IV). Meta-analytic techniques were applied using R software, and pooled VTE proportions with 95% confidence intervals (CIs) were calculated. Heterogeneity was assessed using the I² statistic, and forest plots were generated for visualization. Sensitivity analyses were conducted to evaluate the robustness of findings.Results and discussionThe analysis included 14 studies, out of which hospital-based studies reported a significantly higher VTE proportion (4.1%) compared to population-based studies (2.9%) (p <.001, χ² = 1452.219). Among cancer types, gastrointestinal malignancies had the highest pooled VTE proportions, followed by hematologic and urogenital cancers. In hospital-based cohorts, lung and breast cancers showed particularly high VTE burdens. VTE risk increased with advancing cancer stage, with the highest proportions observed in Stage III and IV cancers. This meta-analysis demonstrates substantial variation in VTE risk based on study setting, cancer type, and stage. The findings underscore the need for nuanced, type- and stage-specific VTE risk assessment models to guide effective prophylaxis and clinical decision-making in oncology practice.Systematic review registrationhttps://www.crd.york.ac.uk/PROSPERO/view/CRD42024616005, identifier CRD42024616005.